2011
DOI: 10.1080/00028487.2011.607050
|View full text |Cite
|
Sign up to set email alerts
|

Size at Release, Size‐Selective Mortality, and Age of Maturity of Willamette River Hatchery Yearling Chinook Salmon

Abstract: We analyzed scales from returning Willamette River yearling Chinook salmon Oncorhynchus tshawytscha to explore the effects of size at release on subsequent adult returns. We tested the hypothesis that survival to adulthood is independent of size at ocean entry for yearling Chinook salmon. Significant size‐selective mortality, indicated by a larger size at ocean entry among surviving adults than among all released juveniles, was observed for Chinook salmon released in 2002–2004 but not for those released in 200… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(42 citation statements)
references
References 42 publications
0
40
0
2
Order By: Relevance
“…Other studies have shown that estuary‐rearing life histories compose 20–35% of returning adults (Jones et al , ). The success rate of individual life histories probably varies from year to year, depending on environmental conditions in freshwater, estuarine and marine environments and potential effects of size‐dependent marine mortality (Bond et al , ; Claiborne et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have shown that estuary‐rearing life histories compose 20–35% of returning adults (Jones et al , ). The success rate of individual life histories probably varies from year to year, depending on environmental conditions in freshwater, estuarine and marine environments and potential effects of size‐dependent marine mortality (Bond et al , ; Claiborne et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Changes observed in the oceanentry size distribution between any of the sample periods (estuary-exit, summer-ocean, fall-ocean) would suggest size-selective mortality. Following Claiborne et al (2011) we used a Wilcoxon rank sum test to compare distributions.…”
Section: Discussionmentioning
confidence: 99%
“…Studies designed to evaluate size-selective mortality have either failed to find evidence of it or have found mixed results (occurring in some but not all years) for Chinook Salmon, including studies focused on Columbia River salmon (Claiborne et al 2011(Claiborne et al , 2014Tomaro et al 2012;Miller et al 2013Miller et al , 2014. Early ocean growth rates estimated from otoliths for three of the stocks included here (and some of the same individuals) were very close to our estimated growth rates (Tomaro et al 2012;Claiborne et al 2014;Miller et al 2014), suggesting that our results are reasonably representative of the true growth rates.…”
Section: Validity Of Ocean Growth Assumptionsmentioning
confidence: 99%
“…Several recent studies of Pacific salmon Oncorhynchus spp. have shown that individuals that survive to adulthood were often larger than average as juveniles (Beamish et al 2004;Zabel and Achord 2004;Moss et al 2005;Claiborne et al 2011; Thompson and Beauchamp 2014), and growth rates during initial marine residence are often correlated with survival in both Atlantic Salmon Salmo salar and Pacific salmon (Holtby et al 1990;Jonsson et al 2003;Miller et al 2014) and marine fish in general (Sogard 1997). However, while variation in timing and size at ocean entry is well documented between species or populations occupying independent river basins (e.g., Groot and Margolis 1991;Quinn 2005;Spence and Hall 2010), far less is known about the variation among populations within basins that enter the ocean at a common location (Beamish et al 2013).…”
mentioning
confidence: 99%